Mitochondrial catastrophe during doxorubicin-induced cardiotoxicity : An evaluation of the protective role of melatonin. - Govender, Yogeshni (Jenelle) (Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.